Acute coronary syndrome in chronic kidney disease: clinical characteristics and stage-wise associations from a tertiary care centre in Western India - Bhatlawande, Tejaswini; Tiwari, Jai Prakash; Edakkunnummel, Hasil Mohammed Ali; Habib, Mudasir; Tyagi, Sumit; Colaco, Joseema; Kar, Bipasa; Nambiar, Anushree; Prabhu, Prarthana; Wani, Saleem Javaid (International Journal of Research in Medical Sciences, 2026)
Background: Cardiovascular disease is the leading cause of morbidity and mortality among patients with chronic kidney disease (CKD). Acute coronary syndrome (ACS) in CKD is often associated with atypical presentations, diagnostic challenges and adverse outcomes. Data from western India regarding the clinical profile of CKD patients presenting with ACS remain limited. Methods: This ambispective observational study was conducted at Goa Medical College, Goa. Adult patients with CKD presenting with ACS between September 2019 and August 2025 were included. Demographic characteristics, comorbidities, clinical presentation, cardiac biomarkers, echocardiographic findings and ACS subtype were assessed. Associations between CKD stage and clinical variables were analysed using the Chi-square test and analysis of variance. Results: A total of 220 patients were included. The mean age was 66.5±9.1 years and 53.2% were male. Hypertension (87.3%), diabetes mellitus (71.8%) and dyslipidemia (66.8%) were common. NSTEMI was the predominant ACS subtype (60%), followed by unstable angina (37.7%) and STEMI (2.3%). Nearly half of patients (45.9%) had atypical presentation. Advancing CKD stage was significantly associated with NSTEMI/STEMI presentation (p<0.001), higher troponin variability (p=0.004), dialysis dependence (p=0.002), higher Killip class (p=0.002) and lower left ventricular ejection fraction (p<0.001). Conclusions: ACS in CKD is characterised by a high burden of cardiovascular risk factors, frequent atypical presentation and predominance of NSTEMI. Advanced CKD is associated with greater cardiac dysfunction and more severe ACS manifestations, highlighting the need for early cardiovascular evaluation and intervention in this population.